PERANCANGAN MEDIA PROMOSI WISATA KUSUMA TIRTA GUNA MENINGKATKAN BRAND AWARENESS - Arifin, Zainul; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: Kusuma Tirta located in Kedung Pelug, District Candi, Sidoarjo. A family recreation area that has the potential of the concept of water attractions are equipped with restaurant, outbound and fishing for the whole family. Pensions Kusuma Tirta Sidoarjo Regent H. Saifulilah inaugurated on June 23, 2012, was not so open this region as a region rekrerasi family, but also as a center of learning and gathering for anyone. Kusuma Tirta Tourism is quite new tour so not so many people who know about the location of this tour, besides the media campaign in Tirta Kusuma tour is also limited and very less active in promoting so many people from the region itself does not know the information sidoarjo on this tour. this led to less familiar travelers about Tirta Kusuma and does not affect the increase in tourists coming to Kusuma Tirta. The problem is Kusuma Tirta is a relatively new tourist spot and less active in the promotion so that tourists, especially in the area of Sidoarjo themselves do not understand the existence of these places, it takes some effort to promote the parawisatawan, one of which is to design a media campaign that is right for Kusuma Tirta can provide information to the public in order to increase brand awareness Kusuma Tirta.Â Keywords: Design, Kusuma Tirta, Brand Awareness